1996
DOI: 10.1074/jbc.271.45.28697
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Regulates Androgen Receptor Hormone Binding Affinity in Vivo

Abstract: The regulation of human androgen receptor (AR) by the molecular chaperone Hsp90 was investigated using the yeast Saccharomyces cerevisiae as a model system. These studies were performed in strains expressing a conditional temperature-sensitive mutant allele of the hsp82 gene, which encodes Hsp90 protein. At the restrictive temperature in the mutant, there is a decrease in hormone-dependent transactivation by the AR, although steady state levels of AR protein are unchanged. Quantitative hormone binding studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
163
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(176 citation statements)
references
References 34 publications
8
163
1
1
Order By: Relevance
“…Previous studies had demonstrated that it is possible to selectively abolish specific dispensable functions of Hsp90 without compromising its ability to ensure viability in yeast; specifically, a variety of HSP82 mutations result in a defect in the regulation of steroid receptors or v-Src or folding of p53 in yeast (Picard et al, 1990;Bohen and Yamamoto, 1993;Xu and Lindquist, 1993;Bohen, 1995;Nathan and Lindquist, 1995;Blagosklonny et al, 1996;Fang et al, 1996;Nathan et al, 1997). We have now considerably extended this theme by showing that even subtle point mutations can discriminate between the Hsp90 requirements in two different signaling pathways.…”
Section: Genetic Dissection Of Different Hsp90 Functionsmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies had demonstrated that it is possible to selectively abolish specific dispensable functions of Hsp90 without compromising its ability to ensure viability in yeast; specifically, a variety of HSP82 mutations result in a defect in the regulation of steroid receptors or v-Src or folding of p53 in yeast (Picard et al, 1990;Bohen and Yamamoto, 1993;Xu and Lindquist, 1993;Bohen, 1995;Nathan and Lindquist, 1995;Blagosklonny et al, 1996;Fang et al, 1996;Nathan et al, 1997). We have now considerably extended this theme by showing that even subtle point mutations can discriminate between the Hsp90 requirements in two different signaling pathways.…”
Section: Genetic Dissection Of Different Hsp90 Functionsmentioning
confidence: 73%
“…Further insights into the role of Hsp90 in the regulation of this particular signal transduction pathway come from studies made in yeast (reviewed in Picard, 1998). Vertebrate steroid receptors expressed in yeast strains with a low level (Picard et al, 1990; see also Holley and Yamamoto, 1995) or specific point mutants of Hsp82 (Bohen and Yamamoto, 1993;Bohen, 1995;Nathan and Lindquist, 1995;Fang et al, 1996) show a defective hormonal response that is due to a decrease in the ligand-binding affinity (Bohen, 1995;Fang et al, 1996). Thus, Hsp90 may have a dual role: it ensures that receptors are kept inactive in the absence of hormone and helps them to respond specifically and efficiently to ligand.…”
Section: Introductionmentioning
confidence: 99%
“…A requirement for Hsp90 in androgen binding to AR was reported previously (27). Geldanamycin, an inhibitor of the Hsp90 chaperone function (58), inhibits androgen binding, increases AR degradation, and inhibits AR functional activity (27,59).…”
Section: Discussionmentioning
confidence: 99%
“…One possible interaction site is the AR ligand-binding domain, which was shown to bind the Hsp70⅐Hsp90 heterocomplex (27,28), and Hsp70⅐Hsp90 interacts with CHIP (23). A recent study demonstrating that CHIP functions as a dimer provides a basis for this type of interaction (29).…”
Section: Fig 3 Interaction Of Chip With the Ar Nh 2 -Terminal Consementioning
confidence: 99%
“…In the absence of a ligand, the AR is associated with Hsp90 in the cytoplasm and kept in a high-affinity hormonebinding conformation necessary for ligand binding. As a consequence, inhibition of the chaperone function of Hsp90 impairs the AR ligand-binding ability (Fang et al, 1996;Georget et al, 2002) With the aim of elucidating the mechanism behind the genotoxic stressinduced loss of AR activity, the ligand-binding ability of the AR in the presence of etoposide and cisplatin was investigated. Hormone-deprived LNCaP cells were stimulated with radiolabeled DHT for 1 h in the presence or absence of etoposide and cisplatin.…”
Section: Genotoxic Stress-induced Inhibition Of Ar Activitymentioning
confidence: 99%